PENJAMINAN HUKUM DALAM INVESTASI DI INDONESIA MELALUI OMNIBUS LAW - Siregar, Emiel Salim; Mangerani, Andi; Ramadani, Sri Aura; Agustian, Rizki; Insani, Gintas Aulia; Manurung, Lila Nurliza; Vanessa, Aprilla Gusti; Putra, Efrangga Dido Aldiansyah; Sari, Rizkia Wita (Peneliti.net, 2024)
This research aims to investigate and analyze the legal certainty of foreign investment laws in Indonesia as outlined in Law Number 25 of 2007 on investment and to explore the analysis of investment regulatory arrangements in Indonesia through the Omnibus Law. The research employs a Normative Juridical method based on secondary legal materials, utilizing both the statute and conceptual approaches. Document study techniques and qualitative analysis are employed for tracing legal materials and analyzing the studies, respectively. The findings reveal that the government plays a crucial role in promoting investment, particularly foreign investment, with expectations of positive impacts on Indonesia's economy, technology transfer, job creation, and overall public welfare. However, legal certainty poses a significant challenge, hindering foreign investors' entry into the country. Issues such as regulatory ambiguity, conflicts between central and local government regulations, and complexities in the licensing bureaucracy are recurrent challenges in investment activities in Indonesia. To address these challenges, the government intends to introduce an Omnibus Law aimed at resolving issues related to investment legal certainty. Nevertheless, while the Omnibus Law provides regulatory certainty, it may not necessarily ensure legal certainty in terms of law enforcement